Screening Ibu Hamil Risiko Tinggi sebagai Upaya Penurunan Angka Kematian Ibu Hamil (AKI) dan Angka Kematian Bayi (AKB) di Desa Langensari Kecamatan Ungaran Barat Kabupaten Semarang - Heni Purwaningsih; Sulastri Sulastri; Sri Mintarsih (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
The maternal mortality rate (MMR) and infant mortality rate (IMR) in Langensari Village, West Ungaran District, Semarang Regency are still relatively high, partly due to the low awareness among pregnant women about the importance of routine pregnancy check-ups. To address this, a high-risk pregnant women screening program was implemented to detect risk factors such as hypertension, gestational diabetes, and anemia early on. The methods used in this program include socialization to the community, medical examinations by trained health workers, and the use of technology in monitoring and referral systems. The screening results showed that out of 100 pregnant women examined, 30% were identified as having high risk, with hypertension being the dominant factor (15%). As many as 90% of high-risk pregnant women were successfully referred and received further care at health facilities. The implementation of this program has proven effective in reducing the risk of pregnancy complications through early intervention and increasing access to adequate healthcare services. Therefore, strengthening the referral system, health education, and increasing the capacity of medical personnel are strategic steps in reducing MMR and IMR in this area. The sustainability and evaluation of this program are crucial to ensure that every pregnant woman receives optimal care, thus preventing serious complications that could potentially endanger the lives of both mothers and infants.